First principles calculations of thermal, equations of state and thermodynamical properties of MgH2 at finite temperatures - Kelkar, Tuhina; Kanhere, Dilip G.; Pal, Sourav (Computational Materials Science, 2008)
We present the first principles calculations of the thermodynamical properties of magnesium hydride (MgH2) over a temperature range of 0-1000 K. The phonon dispersions are determined within the density functional framework and are used to calculate the free energy of MgH2 within the quasiharmonic approximation (QHA) at each cell volume and temperature T. Using the free energies the thermal equation of state (EOS) is derived at several temperatures. From the thermal EOS structural parameters such as the equilibrium bell volume (V-0) and elastic properties, namely, bulk modulus (K-0) and its pressure derivative (K-0(')) are computed. The free energies are also used to calculate various thermodynamical properties within QHA. These include internal energy E, entropy S, specific heat capacity at constant pressure C-P, thermal pressure P-thermal(V,T) and volume thermal expansion Delta V/V (%). The good agreement of calculated values of S and Cp with experimental data exhibits that QHA can be used as a tool for calculating the thermodynamical properties of MgH2 over a wide temperature range. P-thermal(V,T) increases strongly with T at all the volumes but it is a slowly varying function of volume for T = 298-500 K. According to Karki [B.B. Karki, Am. Miner. 85 (2000) 1447] such volume based variations can be neglected and so it is possible to estimate the thermal EOS only with the knowledge of the measured P-thermal(V,T) versus temperature at ambient pressure and isothermal compression data at ambient temperature. Temperature dependence of Delta V/V(%) shows that V-0 increased with increase in temperature. However, the percentage decrease in K-0 superseded this percentage increase in V-0 even at temperatures moderately higher than 298 K. Therefore, we suggest application of temperature (T > 298 K) as an approach to enhance the hydrogen storage capacity of MgH2 because of its better compressibility at these temperatures. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: equation of state; Hydrogen storage; lattice dynamics; magnesium hydride; Thermodynamic properties